Management of eosinophilic esophagitis is often discordant with guidelines and not patient-centered: results of a survey of gastroenterologists. Issue 6 (31st January 2019) - Chang, Joy W; Saini, Sameer D; Mellinger, Jessica L; Chen, Joan W; Zikmund-Fisher, Brian J; Rubenstein, Joel H
Summary: Published guidelines for the management of eosinophilic esophagitis (EoE) recommend an initial trial of proton pump inhibitors (PPI), histologic assessment for response to therapy, and tailoring treatments to patient needs and provider resources. Effectiveness studies directly comparing therapies are lacking, leaving a situation ripe for shared decision making. We aimed to assess gastroenterologists' adherence to guidelines and how they respond to EoE patients' preferences regarding management. We administered a web-based survey to practicing US gastroenterologists, assessing knowledge, and practice patterns in the management of EoE, including comfort with alternative treatments to steroids. Ninety-two providers responded, including 55% in private practice. Nearly half (47%) reported spending ≤10 minutes on initial education and counseling and 48% recommended PPI monotherapy prior to other strategies. Of those who did not start with PPI monotherapy, 55% chose topical steroids ± PPI and 26% dietary elimination ± PPI. Despite this, 90% felt comfortable allowing a patient to start dietary elimination instead of steroids, but less comfortable with dilation alone (39%) or no treatment (30%). Upon symptomatic resolution, 72% of academic providers recommended endoscopy with biopsies to demonstrate histologic response to treatment, compared to 27% in private practice. There are substantial variations in adherence to guidelines regarding PPI use and assessing response to therapy. Gastroenterologists prefer topical steroids over other treatment modalities and most spend little time educating and counseling, which may limit informed decision making. Strategies aimed at decreasing these variations in management and promoting shared decision making in EoE are needed.